The impact of using parables as a teaching method on enhancing Islamic values among 7th-grade students in Jordan - Mousa, Ala’a-Deen Zaki Ali; Alsalti, Mahmoud (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores the impact of using parables as a teaching method on enhancing Islamic values among 7th-grade students in Jordan. The quasi-experimental design, along with experimental and control group design, was used. The research sample consisted of 56 male and female students from a public school in Amman. The sample participants were randomly divided into an experimental group, taught using Arabic parables and related video clips, and a control group, taught using the traditional lecture method. A pre- and post-test of Islamic values, utilized as a research instrument, was administered to measure students’ level of understanding of the targeted Islamic values such as honesty, loyalty, and belonging, and their attitudes toward them. After analyzing the data using appropriate statistical tests, the research results demonstrated statistically significant differences at the significance level (α = 0.05) between the means of performance of the two groups in the post-test in favor of the experimental group, accentuating the effectiveness of the method of parables in developing Islamic values among students. This paper is of high significance as it calls for incorporating parables and meaningful stories into Islamic education curricula to teach values and train teachers to use them optimally. That said, among the key recommendations is the integration of parables into the curriculum by including meaningful Arabic parables in Islamic education, national education, and Arabic language courses, as part of activities or exercises accompanying lessons.